Tariff Equilibrium with Customs Union (The Pakistan Development Review, 1994)
It is well known from Kemp and Wan (1976) that under customs union an increase in group welfare can occur without affecting that of the rest of the world whenever the common external tariff is positioned in a way so as to offset exactly the terms of trade and export quantity effects felt by it. The purpose of this paper is to study the effects of the customs union starting from arbitrary given initial tariff rates and determine cases when the union as well as the non-union countries may gain from the formation of the customs union.